2005
DOI: 10.1126/science.1105166
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 Dimerization Regulated by Reversible Acetylation of a Single Lysine Residue

Abstract: Upon cytokine treatment, members of the signal transducers and activators of transcription (STAT) family of proteins are phosphorylated on tyrosine and serine sites within the carboxyl-terminal region in cells. We show that in response to cytokine treatment, Stat3 is also acetylated on a single lysine residue, Lys685. Histone acetyltransferase p300-mediated Stat3 acetylation on Lys685 was reversible by type I histone deacetylase (HDAC). Use of a prostate cancer cell line (PC3) that lacks Stat3 and PC3 cells ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
628
3
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 685 publications
(661 citation statements)
references
References 26 publications
27
628
3
3
Order By: Relevance
“…4). It is possible that LIF may influence glial gene expression by enhancing the association between STAT3 and CBP, as previously reported 36 . Consistent with this hypothesis, ChIP analyses indicated that LIF enhanced the recruitment of CBP to the GFAP promoter, likely through STAT3C (Fig.…”
Section: A Positive Autoregulatory Loop Of the Jak-stat Machinerysupporting
confidence: 58%
See 1 more Smart Citation
“…4). It is possible that LIF may influence glial gene expression by enhancing the association between STAT3 and CBP, as previously reported 36 . Consistent with this hypothesis, ChIP analyses indicated that LIF enhanced the recruitment of CBP to the GFAP promoter, likely through STAT3C (Fig.…”
Section: A Positive Autoregulatory Loop Of the Jak-stat Machinerysupporting
confidence: 58%
“…6a). LIF stimulation further increased the activity of the promoter, potentially by increasing STAT1/3 serine phosphorylation or by recruiting more endogenous pSTAT1/3 or CBP to the transcriptional machinery 36 . Western blot analyses indicated that overexpression of STAT3C in 3-DIV E11 cortical NPCs increased the overall activity of the Jak-STAT machinery as reflected by increased tyrosine (Tyr701 or Tyr705) and serine (Ser727) phosphorylation of STAT1/3 as well as increased protein levels of STAT1 and receptor gp130 (Fig.…”
Section: A Positive Autoregulatory Loop Of the Jak-stat Machinerymentioning
confidence: 99%
“…A direct interaction of KAP1 with HDACs is also proposed to be a mechanism for transcriptional repression by KAP1 (Underhill et al, 2000;Satou et al, 2001;Schultz et al, 2001). It has also been demonstrated that STAT3 associates with HDAC3 and that trichostatin A, an HDAC inhibitor, restores its transcriptional activity (Yuan et al, 2005). We tested the effects of KAP1 on interactions between STAT3 and HDAC3.…”
Section: Interactions Between Stat3 and Kap1mentioning
confidence: 96%
“…As already described for some factors (STAT3 and BAX), reversibile acetylation affects the subcellular localization of several proteins. In some cases, the nuclear localization signal contains acetylatable lysine residues that favour nuclear retention when acetylated 23 . In the case of the multifunctional HMG box 1 (HMGB1) protein, acetylation favours nuclear export and cytosolic accumulation before secretion during inflammatory and/or necrotic processes 29 .…”
Section: At a Glancementioning
confidence: 99%
“…This confers either potentiation of transcriptional activity or destabilization of the enhanceosome and termination of the transcriptional response 22 . In the case of the transcription factor signal transducer and activator of transcription 3 (STAT3), which is activated by cytokine signalling, cytosolic acetylation triggers STAT3 dimerization and subsequent nuclear translocation 23,24 . Acetylation of hypoxia-inducible factor 1 (HIF1) by the ARD1 HAT apparently leads to increased association with the von Hippel-Lindau (VHL) ubiquitylation complex and proteasome-mediated degradation, which has a regulatory role in the cellular response to changes in oxygen availability and angiogenesis 25,26 .…”
mentioning
confidence: 99%